PENGARUH FAKTOR – FAKTOR KEPUASAN KERJA TERHADAP DISIPLIN KERJA KARYAWAN PADA UKM MANIK-MANIK DI DESA GAMBANG KECAMATAN GUDO KABUPATEN JOMBANG - Cahyo Tri Atmojo; Fahimul Amri (INSTITUT TEKNOLOGI DAN BISNIS PGRI DEWANTARA JOMBANG, 2015)
SMEs are an important part of the economy of a country or region. In the face of competition and challenges businesses increasingly stringent in the days of today's modern era, every SMEs is required to be able to carry out the restructuring and reorganization with the aim that SMEs can adjust to the conditions of the times, and to meet consumer demand for more and more specific, changing rapidly, high quality products and low prices. To meet these goals in the competition, every employer is required to pay attention to their employees' job satisfaction to create the discipline of employees and expected impact on the creation of competitive products and the fulfillment of consumer demand for the product. Type of associative research using quantitative descriptive approach. The population in this study were all employees of SMEs Beads On Di Desa Impiana Jombang District of Gudo, there were 445 respondents. Precision sample used is 10% of the total population that is 82 respondents. The technique of collecting data using questionnaires and documentation. Data were analyzed using multiple linear regression. This study shows there are factors influence job satisfaction include psychological factors, physical factors, factors financial, Social Factors to the discipline of employees in SMEs beads in the village xylophone districts Gudo district jombang with F test results indicate that Fhitung 12.563> Ftable = 3.11 and 0.000 sig value of <0.05. and social factors are the dominant influence on the discipline of employees in SMEs beads in the village xylophone districts Gudo district jombang with Beta value = 0.865 and greater than the psychological factors (0.445), physical factors (0.034), as well as financial factors (0,025)